Understanding the locus of control of management students - an exploratory study. (2017) - Bharathi, S. Vijayakumar; Joseph, Shaji
This research examines the impact of locus of control in the academic life of management students. A customised locus of control inventory is proposed which was administered to a sample of 170 management students in India. Using exploratory factor analysis, seven components were identified as influencers of locus of control throughout the academic life of a management student namely destiny, academic performance, introversion, attribution effect, luck, self-efficacy and self-confidence. Moreover, the study finds that the predominant locus of control is external except in case of self-efficacy and self-confidence. The outcome of the research also suggested technology, participant-centred pedagogy and mentoring as the key constructs for future research work in locus of control.